An assessment of semi-analytical models based on the absorption coefficient in retrieving the chlorophyll-a concentration from a reservoir - Andrade, Caroline [UNESP]; Alcantara, Enner [UNESP]; Bernardo, Nariane [UNESP]; Kampel, Milton (Elsevier B.V., 2019)
Monitoring chlorophyll-a (Chl-a) concentrations in inland waters is crucial for water quality management, since Chl-a is a proxy for phytoplankton biomass and, thus, for ecological health of a water environment. Chl-a concentration can be retrieved through the inherent optical properties (IOPs) of a water system, which, in turn, can be remotely sensed obtained. Quasi-analytical algorithm (QAA), originally developed for ocean waters, can also retrieve IOPs for inland waters after re-parameterizations. This study is aimed at assessing the performance of sixteen schemes composed by QAA original and re-parameterized versions followed by models that use absorption coefficients as inputs for estimating Chl-a concentration in Ibitinga reservoir, located at Tiete River cascading system, Sao Paulo State, Brazil. It was verified that only QAA(v5) based schemes were able to obtain reasonable estimates for image data and that by four models tested presented similar and acceptable results for QAA(v5) outputs. The best model were applied to a Ocean and Land Colour Instrument (OLCI) image. Light absorption in the reservoir showed to be dominated by colored dissolved organic matter (CDOM), and wide spatial and temporal variability of optical and water quality properties was observed. (C) 2018 COSPAR. Published by Elsevier Ltd. All rights reserved.
Keywords: Trophic status; Water quality monitoring; Inland water; Satellite data